2015
DOI: 10.1093/gji/ggv396
|View full text |Cite
|
Sign up to set email alerts
|

Australia's lithospheric density field, and its isostatic equilibration

Abstract: Density is a key driver of tectonic processes, but it is a difficult property to define well in the lithosphere because the gravity method is non-unique, and because converting to density from seismic velocity models, themselves non-unique, is also highly uncertain. Here we use a new approach to define the lithospheric density field of Australia, covering from 100 • E to 165 • E, from 5 • N to 55 • S and from the crust surface to 300 km depth. A reference model was derived primarily from the recently released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…The AuSREM density distribution was taken as starting point by Aitken et al (2015), who undertook a 3-D inversion to fit the observed gravity field across Australia. The gravity data employed combine both satellite and near-surface gravity observations, with the removal of a continental-scale gravity field linked to the density variations in the upper mantle.…”
Section: Density Structurementioning
confidence: 99%
“…The AuSREM density distribution was taken as starting point by Aitken et al (2015), who undertook a 3-D inversion to fit the observed gravity field across Australia. The gravity data employed combine both satellite and near-surface gravity observations, with the removal of a continental-scale gravity field linked to the density variations in the upper mantle.…”
Section: Density Structurementioning
confidence: 99%
“…A global reference model of the lithosphere 1603 models in regional gravity and/or isostatic studies (e.g. Mechie et al 2013;Levandowski et al 2014;Aitken et al 2015), as input in global circulation/convection models and dynamic topography studies (e.g. Flament et al 2013;Becker et al 2014;Steinberger 2016), as anchor points in the interpretation of a number of geochemical data (cf.…”
mentioning
confidence: 99%
“…We define density anomaly ρ = ρ 0 m 1 and magnetic susceptibility χ = χ 0 e m 2 for unknown property functions m 1 and m 2 , reference density ρ 0 and reference magnetic susceptibility χ 0 . Reference quantities ρ 0 and χ 0 can be constant or functions of their location if prior information is available (Aitken et al 2015). The PDEs are…”
Section: T H E I N V E R S I O N P Ro B L E Mmentioning
confidence: 99%
“…However, this weighting is spatially variable and consistent with nonlinear conjugate gradient solvers. In the next section various options for weighting are introduced within the inversion framework of , based on a coherent formulation using partial differential equations (PDEs) and the finite element method (FEM; see also Aitken et al 2015;Codd & Gross 2018). Several approaches to modify the cross-gradient function are presented in Section 3.…”
Section: Introductionmentioning
confidence: 99%